Intersectional Feminist Community Transformation: Women’s Reproduktive Health Innovation Within Patriarchal Hegemony - Handayani, Asri Reni; Harmili; Asmanengsi, Sarti (Dinasti Research, 2025)
Reproductive rights signify women’s autonomy; however, many women still lack full control over their own bodies. Unequal gender norms often place women at a disadvantage in negotiating the use and control of their reproductive organs. Patriarchal hegemony reinforces women’s subordination by restricting their rights to information, access to healthcare services, and control over their bodily autonomy. Health systems that are not grounded in gender equality frequently fail to address women’s specific needs, leading to limited access to essential reproductive health information and services. This study aims to examine and analyze community transformation through an intersectional feminist approach, focusing on women’s reproductive health innovations as a means to promote gender equality within patriarchal structures. The research employs a normative–empirical legal method, combining doctrinal analysis with field investigation. Primary data were collected through open-ended and in-depth interviews with selected participants, and analyzed qualitatively to explore women’s experiences, perceptions, and constraints regarding reproductive rights. The findings reveal that women’s understanding of and access to reproductive health rights in Sumbawa remain constrained by entrenched patriarchal norms, low literacy levels, gender-insensitive healthcare services, and minimal male involvement in family planning programs. Nonetheless, initiatives such as the Ayah Asih (Caring Fathers) program and posyandu remaja (youth health posts) have been introduced to foster gender equality and increase reproductive health awareness. Although women’s reproductive rights are legally recognized in Indonesia, their implementation remains limited, and women continue to face significant challenges in asserting their reproductive autonomy.